2000
DOI: 10.3141/1716-03
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture on Modulus Values of Base and Subgrade Materials

Abstract: Moisture in the base and subgrade layers of pavement can significantly decrease the modulus values of these layers. Recently, a study was performed on several Florida state roads for the purpose of evaluating the decrease in moduli of bases and subgrades due to the proximity of the water table. Dynaflect and falling weight deflectometer (FWD) tests were performed on pavement test sections throughout Florida for the purpose of backcalculation of the modulus values of the different layers. Testing was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…The effects of moisture content and suction on soil resilient modulus have been reported by several authors (3,(6)(7)(8)(9)(10)(11)(12)(13)(14). Such effects may be quantified in the laboratory or in in situ tests.…”
Section: Overviewmentioning
confidence: 81%
“…The effects of moisture content and suction on soil resilient modulus have been reported by several authors (3,(6)(7)(8)(9)(10)(11)(12)(13)(14). Such effects may be quantified in the laboratory or in in situ tests.…”
Section: Overviewmentioning
confidence: 81%
“…It is generally caused by segregation in the construction process, which is presented as poorly bonding and compaction [10]. This category of distress is so-called potential damage because it is hard to detect with little change in its extrinsic feature at the initial phase but the strength has been loosened [11]. When it bears certain loading, a sudden breakdown may happen on the road surface [12].…”
Section: Moisture Damage and Potential Distressmentioning
confidence: 99%
“…Various factors including moisture content, plasticity index, and vertical stresses can affect the stiffness of subgrade and subbase. Ksaibati et al (2000) have studied the effect of moisture content in the stiffness of the subbase. They found that moisture content increases as the depth of the ground water decreases.…”
Section: Variation In the Stiffness Of Subgradementioning
confidence: 99%